3D-printed scaffold combined to 2D osteoinductive coatings to repair a critical-size mandibular bone defect - Bouyer, M. (Mater Today Bio, 2021)
The reconstruction of large bone defects (12 cm(3)) remains a challenge for clinicians. We developed a new critical-size mandibular bone defect model on a minipig, close to human clinical issues. We analyzed the bone reconstruction obtained by a 3D-printed scaffold made of clinical-grade polylactic acid (PLA), coated with a polyelectrolyte film delivering an osteogenic bioactive molecule (BMP-2). We compared the results (computed tomography scans, microcomputed tomography scans, histology) to the gold standard solution, bone autograft. We demonstrated that the dose of BMP-2 delivered from the scaffold significantly influenced the amount of regenerated bone and the repair kinetics, with a clear BMP-2 dose-dependence. Bone was homogeneously formed inside the scaffold without ectopic bone formation. The bone repair was as good as for the bone autograft. The BMP-2 doses applied in our study were reduced 20- to 75-fold compared to the commercial collagen sponges used in the current clinical applications, without any adverse effects. Three-dimensional printed PLA scaffolds loaded with reduced doses of BMP-2 may be a safe and simple solution for large bone defects faced in the clinic.